Activating & engaging habits of mind - Costa, Arthur L.; Kallick, Bena. (Alexandria, VA : Association for Supervision and Curriculum Development, 2000)
Presents practical advice for using the "habits of mind"--sixteen types of intelligent behavior--in the classroom, including discussion of their application to mathematics, art, foreign language, reading comprehension, and character instruction.
"ASCD product no. 100033"--T.p. verso.
Spine title: Activating and engaging habits of mind.
Includes bibliographical references and index.
Professional
Keywords: Cognition in children; Effective teaching -- United States; Thought and thinking -- Study and teaching -- United States; Teaching -- United States; Theory of knowledge; Thought and thinking -- Study and teaching -- United States